A novel method for automating the checking and correction of digital elevation models using orthophotographs - Georgopoulos, Andreas; Skarlatos, Dimitrios (My University, 2003)
This article presents a complete mathematical model, which translates discrepancies between two orthophotographs created from different photographs, into precise corrections of the Digital Elevation Model (DEM). These corrections are the differences from the real surface and, if applied over the existing DEM, can produce a more accurate one. The mathematical model is straightforward, and is not approximate, and therefore there is no need for iterations. Possible applications include checking of automatically created DEMs, refinement of existing DEMs using aerial photographs and update of orthophotographs based on the previous DEM and new imagery.
Keywords: Automatic; Checking; Correcting; DEM; Mathematical model; Orthophotographs